Clear sky solar irradiance models: A review of seventy models. (June 2019) - Antonanzas-Torres, F.; Urraca, R.; Polo, J.; Perpiñán-Lamigueiro, O.; Escobar, R.
Abstract: Clear sky solar irradiance parametric models seek to simplify the atmospheric attenuation with relatively simple parameterizations in order to estimate solar irradiance under clear sky conditions, avoiding the use of computationally expensive radiative transfer models. These models are particularly useful when estimating solar irradiation with satellite retrievals. Due to the great number of clear sky parametric models, it is somehow complicated to decide the choice of model to be selected. This article continues the work of previous reviews of clear sky models adding new models up to seventy described models for diffuse, beam and global components. A model benchmark is performed with ancillary solar irradiance data from two meteorological stations belonging to the Baseline Surface Radiation Network (BSRN) and also ancillary aerosol data from the Aerosol Robotic Network (AERONET). Results show great differences in performance between models, leading to priorize the use of only a few of them. Besides the review and evaluation of models, one of the most valuable deliverables of this paper is theR code of each clear sky model provided in a public GitHub repository (http://www.github.com/EDMANSolar/pcsol ).